2018
DOI: 10.4103/0366-6999.223852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Pelvic Peritonization in Laparoscopic Dixon Surgery

Abstract: Background:Pelvic floor peritoneum reconstruction is a key step in various standard resections for open radical rectal cancer. However, during endoscopic surgery, most surgeons do not close the pelvic floor peritoneum. This study aims to evaluate the efficacy of pelvic peritonization during laparoscopic Dixon surgery using an observational study.Methods:A total of 189 patients, who underwent laparoscopic Dixon surgery at Tianjin Union Medical Center, China, were analyzed retrospectively. All of the cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Few studies have reported the outcome of PC during LAR of rectal cancer; most surgeons believe that it did not change long‐ or short‐term outcomes. However, while a recent study reported that PC in Dixon surgery reduced the occurrence of AL and adhesive intestinal obstruction 9 ; therefore, the outcomes of PC need further study.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Few studies have reported the outcome of PC during LAR of rectal cancer; most surgeons believe that it did not change long‐ or short‐term outcomes. However, while a recent study reported that PC in Dixon surgery reduced the occurrence of AL and adhesive intestinal obstruction 9 ; therefore, the outcomes of PC need further study.…”
Section: Introductionmentioning
confidence: 95%
“…Pelvic floor peritoneum closure (PC) is a key step in various standard resections for open radical rectal cancer surgery. 9 However, PC in endoscopic LAR is not routine and remains controversial, partly due to the technical difficulties and time required for suturing. Few studies have reported the outcome of PC during LAR of rectal cancer; most surgeons believe that it did not change long-or short-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Напротив, установлено, что укрепление швов колоректального аппаратного анастомоза имело статистическую достоверность в повышении риска НА (ОР 2,352; 95 % ДИ 1,112-5,00; p = 0,027). Однако при многофакторном анализе уже не было показано [38]. Авторы отмечали статистически значимое снижение НА в группе пациентов, которым тазовая брюшина была восстановлена (p = 0,014).…”
Section: обсуждение и выводыunclassified
“…с участием 584 пациентов, говорящие о том, что частота развития НА достоверно сопоставима в группах с ушиванием и без ушивания тазовой брюшины, но частота повторных операций по поводу НА в группе пациентов с ушиванием тазовой брюшины достоверно ниже (36,4 % против 11,1 %; р = 0,025) [55]. Еще одно китайское исследование с участием 189 пациентов показало, что ушивание тазовой брюшины не только снижает риск повторных операций, но и уменьшает частоту развития НА (р = 0,14) [56].…”
Section: методы профилактики развития несостоятельности анастомозовunclassified